2017
DOI: 10.1055/s-0037-1602656
|View full text |Cite
|
Sign up to set email alerts
|

How Should We Treat HAP/VAP Caused by Carbapenemase-Producing Enterobacteriaceae?

Abstract: Hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) represent a common problem in hospital setting worldwide. Infections caused by carbapenem-resistant Enterobacteriaceae (CRE) are an emergent problem due to the lack of therapeutic options available, leading to significant increases in morbidity and mortality. CRE have frequently been reported both in HAP/VAP, but limited data regarding the optimal treatment strategy in this setting are available. This review focuses on the current epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The findings of this study, where meropenem-vaborbactam, aminoglycosides, carbapenems, and tigecycline were the only agents displaying susceptibility rates Ͼ90% against 4,790 Enterobacterales isolates, reinforce the challenges to improve care for patients with HAP/VAP, for which delayed and inadequate treatments have been associated with increased rates of morbidity and mortality (25,26). Similar results were observed when these agents were tested against a worldwide collection of Enterobacterales recovered from different infection sources (12).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…The findings of this study, where meropenem-vaborbactam, aminoglycosides, carbapenems, and tigecycline were the only agents displaying susceptibility rates Ͼ90% against 4,790 Enterobacterales isolates, reinforce the challenges to improve care for patients with HAP/VAP, for which delayed and inadequate treatments have been associated with increased rates of morbidity and mortality (25,26). Similar results were observed when these agents were tested against a worldwide collection of Enterobacterales recovered from different infection sources (12).…”
supporting
confidence: 69%
“…The emergence and widespread geography of CRE isolates have added considerable challenges to treating severe infections, and mortality rates are as high as 40% to 50% (27)(28)(29). Therapeutic options to treat CRE HAP/VAP infections are limited, and traditionally, agents from either the polymyxin or aminoglycoside classes have been recommended in combined therapy, usually with carbapenem-containing regimens (1,26,30,31). However, studies have shown that colistin, tigecycline, and gentamicin have poor lung penetration, whereas carbapenems have good distribution in lungs, achieving clinically relevant concentrations (26,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus is the leading cause of nosocomial pneumonia, followed by Pseudomonas aeruginosa and Klebsiella/Enterobacter species. The occurrence of multidrug-resistant Gram-negative organisms in nosocomial pneumonia differs according to the hospital and geographic region (5, 7), but P. aeruginosa isolates are intrinsically resistant to multiple antimicrobial agents, and Klebsiella and Enterobacter species have been shown to have increasing rates of resistance to several antimicrobial agents; therefore, the therapeutic options for treating nosocomial pneumonia caused by Gram-negative organisms are limited (8,9).…”
mentioning
confidence: 99%
“…CAZ-AVI, a promising option for the treatment of carbapenem-resistant Gram-negative bacteria, has been approved by the US Food and Drug Administration (FDA) and European Medicines Agency for the treatment of HAP/ VAP owing to its attractive bactericidal broadspectrum activity, linear pharmacokinetics with a moderate degree of lung penetration, and low risk of serious adverse events [35]. Previous studies have shown the efficacy of CAZ-AVI in the treatment of CRE infection, including CRKP, with low mortality and recurrence rates even following monotherapy [14,20,[36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%